The Effectiveness of Problem-Based Learning Model Assisted by Interactive Video in Improving Science Literacy of Students in Elementary School - Agesti Purnaning Putri; Sigit Saptono; Udi Utomo (Universitas Negeri Semarang, 2022)
Science learning in elementary schools requires competent teachers and adequate learning facilities. This study aims to analyze the effectiveness and determine the responses of teachers and students to the application of the interactive video with PBL model in improving the scientific literacy of fifth-grade elementary school. This study used a quasi-experimental research design. The samples of this study were 18 students of class V SD Lerep 02 as the experimental class, and class V SDN Lerep 05 as the control class as many as 21 students. Data were collected using interview techniques, questionnaires, observations, and scientific literacy tests. Data analysis techniques using descriptive test, paired test, N-gain, independent t-test, and response analysis were also carried out to determine student and teacher responses to the applied learning model. The results of this study indicate that 1) the application of the interactive video with PBL model is effective in improving the scientific literacy of fifth grade elementary school students. These results are shown by the experimental class scientific literacy results which are significantly higher than that of the control class with an average value of 84.22% and the results of observations show that 60% of students in each post-learning scientific literacy can increase. 2) Students gave a very good response to the application of the interactive video with PBL model with an average response score of 87.22%. So, it can be concluded that the PBL learning model assisted by interactive video is effective in improving scientific literacy of students in elementary school.